2022
DOI: 10.1177/10870547221112941
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Treatment Outcomes in Children and Adolescents With ADHD to Other Disorders Within an Australian and Dutch Outpatient Cohort

Abstract: Objective: Previous studies at child and youth mental health services (CYMHS) suggest that children with ADHD have poorer outcomes compared to those with other diagnoses. This study investigates this in more detail. Methods: Children with ADHD were compared to those with ASD and those with emotional disorders, on routinely collected outcomes at CYMHS in Australia ( N = 2,513) and the Netherlands ( N = 844). Results: Where the emotional disorders group reached a similar level of emotional symptoms at the end-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…This good response to treatment of comorbid emotional conditions is in line with the findings of Gould and colleagues, 17 who found the presence of comorbid ADHD did not affect treatment outcomes of CBT for anxiety disorders. The poorer response to treatment for attention symptoms found by our group 15 is in line with previous studies. [18][19][20] A notable discrepancy is that these findings of suboptimal improvements in attention symptoms in clinical settings are in contrast to the good outcomes reported in medication treatment trials.…”
Section: Open Accesssupporting
confidence: 93%
See 4 more Smart Citations
“…This good response to treatment of comorbid emotional conditions is in line with the findings of Gould and colleagues, 17 who found the presence of comorbid ADHD did not affect treatment outcomes of CBT for anxiety disorders. The poorer response to treatment for attention symptoms found by our group 15 is in line with previous studies. [18][19][20] A notable discrepancy is that these findings of suboptimal improvements in attention symptoms in clinical settings are in contrast to the good outcomes reported in medication treatment trials.…”
Section: Open Accesssupporting
confidence: 93%
“…Children under the care of these services may experience a treatment ceiling; having already received evidence-based treatment from a primary care provider, there may be fewer gains to be made in the public system. This was confirmed by Payne et al , 15 who showed that the severity of symptoms in children attending CYMHS in Queensland, Australia, played a role in explaining poorer routine outcome measure improvement. Few studies have explored the treatment provided to children with ADHD.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations